Double trisomy (XXX+21 karyotype) in a six-year-old girl with down phenotype (2018)
We describe a case of a six-year-old girl who presents multiple dysmorphic features characteristic of Down’s syndrome. She has a significant general developmental delay, with a score that correspond to 32 months of developmental age. This delay is especially in language, with a very scant vocabulary. She communicates with some hand sign words or pointing, although her auditory responses in hearing test were normal. Two previous karyotype studies showed 47, XXX, +21 anomalies. This double trisomy is a rare condition described in isolated cases in the literature and none of these refers to the developmental aspects of these children (Balwan et al.2008; Li et al.2004; Park et al.1995; Day et al.1963). © 2018, Indian Academy of Sciences.